E-Government Sebagai Upaya Dalam Meningkatkan Kualitas Pelayanan Publik Di Kabupaten Pamekasan - Anisa Kurniatul Azizah; Laili Dwi Agustina (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Bhayangkara Surabaya, 2023)
The purpose of this study is to analyze and study E-Government as an effort to improve the quality of public services in Pamekasan Regency. Pamekasan Regency applies the concept of E-Government in the form of an application, but is still experiencing difficulties in the development planning process. This research is a qualitative research with research subjects namely Pamekasan Regency. The research method used is observation and documentation techniques. The results of the study show that the government has succeeded in innovating in the form of